2014
DOI: 10.1215/1089201x-2648623
|View full text |Cite
|
Sign up to set email alerts
|

Money, Peasant Mobility, Çiftliks, and Local Politics in Salonika

Abstract: This study explores how the monetization and commercialization of rural economy, peasant mobility, and the changing power of landholders in the countryside affected the nature of Salonikan society throughout the eighteenth century. It analyzes the ways in which the emerging power relations in rural areas altered both the status of different social groups and the contours of local administration in an Ottoman provincial setting. It aims to show that the new rural-urban dynamics not only shaped the political all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…In the region around Ruse prominent members of the provincial and central elite began to form large estates and consolidate their power in the countryside earlier than their peers in Vidin and Salonika (McGowan 1981, p. 217; İnalcık 1998, pp. 29–30; Kokdas 2014, pp. 139–44).…”
Section: IVmentioning
confidence: 99%
“…In the region around Ruse prominent members of the provincial and central elite began to form large estates and consolidate their power in the countryside earlier than their peers in Vidin and Salonika (McGowan 1981, p. 217; İnalcık 1998, pp. 29–30; Kokdas 2014, pp. 139–44).…”
Section: IVmentioning
confidence: 99%
“…From among those who have worked on the eighteenth-century Balkans, Sophia Laiou has shown that çiftliks in western Thessaly were formed legitimately on both private and state land; that in the latter case peasants had to bear the extra burden of making payments not only to the timar holder whom the state had appointed as the rightful recipient of dues but also to the çiftlik holder who occupied a place in between the peasants and the timar holder; and that long-term tax-collection rights could lead to de facto rights of ownership over an area (Laiou 2007: 268-270, 274-276). İrfan Kokdaş has argued that sharecropping, patronage, and credit relations formed a triangle that pervaded urban elite-peasant relations in the context of chiftlicisation; that the protection that landholders could provide against taxation and outlaws was an incentive for peasants to abandon their villages and settle on çiftliks; and that çiftlik-holding translated into political capital (Kokdas 2014). Based on probate inventories from Thessaloniki, Phokion Kotzageorgis and Demetrios Papastamatiou have confirmed that landholding and being owed amounts of money (most likely from moneylending) were two assets which typically were combined in the properties of the wealthy, while Papastamatiou has demonstrated that çiftliks were owned mostly by a military-dominated elite of wealthy Thessalonians, and were low-investment and intensity productive units whose production was nevertheless intended for the market (Kotzageorgis, Papastamatiou 2014: 171-178;Papastamatiou 2014;Papastamatiou 2017: 225-231).…”
mentioning
confidence: 99%